EFFECT OF DIFFERENT DIETARY ENERGY LEVELS ON MILK PRODUCTION IN LACTATING NILI-RAVI BUFFALOES - M. A. Jabbar; M. Fiaz; T. Iqbal; M. Abdullah; I. B. Marghazani (Journal of Animal and Plant Sciences, 2013)
Multiparous lactating Nili-Ravi buffaloes (n= 27) were selected and randomly divided into three groups with nine animals in each under a completely randomized design. Three diets were formulated, being iso-nitrogenous but having varying energy levels, viz; E-100 (Control), E-80 and E-120; E reflecting energy followed by percentage energy in relation to NRC recommended levels for lactating cows. Milk yield did not differ between diets E-100 and E-120 (10.63±0.165 and 10.87±0.124 kg/day, respectively) but was lower (P0.05) among the dietary treatments. However, feed efficiency in terms of fat corrected milk (FCM) per unit /DMI was lower (P<0.05) in animals fed diet E- 80 (0.89 ± 0.019) than those on the other two treatments. Likewise, cost of feed per kg FCM was higher (P<0.05) in this group (17.85 ± 0.28 PK-Rs). It was concluded that feeding lactating Nili- Ravi buffaloes a diet containing more ( i.e., 120 %) than the NRC level of ME recommended for large breed dairy cows conferred no advantage whilst feeding a diet containing less than the recommended level decreased both milk production and feed efficiency.
Keywords: Dietary energy; lactation performance; Nili-Ravi. Buffalo